Substance Use Disorder: Experiences of Affected Family Members Social Support - (:unkn) unknown (My University, 2020)
ABSTRACT Substance Use Disorder: Experiences of Affected Family Members Social Support by Eileen Kane The University of Wisconsin- Milwaukee, 2020 Under the Supervision of Dr. Julia Snethen Background: Social support is a factor in the health and well-being of all populations (WHO, 2018). Having a loved one with SUD negatively affects family members. Affected Family Members (AFM) providing support for the individual with ISUD, are at risk of losing their social support network. Losing social support negatively influences AFMs health and well-being. The purpose of this study was to explore the affected family member (AFM) of an individual with a substance use disorder (ISUD) perceptions and experiences of social support. A secondary purpose was to examine the association of social support and how it contributes to the health and well-being of the AFM of an ISUD. Methods: A mixed methods cross-sectional study was conducted using a convenience sample (N=134) of AFM’s. Participants completed an anonymous survey, including participant characteristics, the Alcohol, Drugs, and Family Social Support Scale (ADF SSS), and the Public Health Surveillance Well-Being Scale (PHS-WS). A subsample of n =101 completed the open-ended questions with n = 1088 responses received. Findings: Positive social support is significantly associated with increased health and wellbeing of the AFM r (133) = .25, p = .004. Additionally, five themes emerged from the qualitative analysis. (1) We are all alone, and we have to fend for ourselves. (2) No one understands what we are going through. (3) Healthcare providers do not know how to provide care and are clueless. (4) We have no access to effective care or treatment. (5) People cannot relate and recoil from us. Discussion: The AFMs perceptions and experiences of social support impacts the stress and burden of care for the ISUD. The positive or negative social support of the AFM influences their feelings of health and well-being.
Keywords: Addiction; Affected Family Member; Drug; Family; Individual; Substance Use Disorder